Extranodal Non-Hodgkin’s Lymphoma at Maxillofacial Bone: A Case Report - Wardhana, Thomas Arie Satya; Adiputra, Putu Anda Tusta (JBN (Jurnal Bedah Nasional); Vol 3 No 2 (2019): JBN (Jurnal Bedah Nasional), 2019)
Background : Extranodal lymphoma appears in about 40% of all lymphoma patients and has been reported in almost all tissue and organs. The most common site is the intestinal tract, followed by head and neck. There are many reports about extranodal lymphomas that arise in orbits, paranasal sinus and oral cavities, nasal, thyroid and salivary glands. These lymphomas usually do not destroy adjacent bone, unlike squamous cell carcinoma. Case: We would like to present an uncommon case of diffuse large B-cell extranodal lymphoma arising maxillofacial bone on buccal area that infiltrating to maxillary sinus and orbital, with bone destruction as well. The patient responded well with CEOP regimen chemotherapy and showed significant tumor regression with symptoms reduction. She just underwent the seventh series of chemotherapy now and planned to be restaging after eighth chemotherapy. Conclusion: Chemotherapy remains the treatment of choice for non-Hodgkin lymphomas. Surgery also takes place in modality choice of treatment of maxillary cancer, either a partial or total maxillectomy alone, or maxillectomy with craniofacial resection.